Design of solar photovoltaic pressurized drip irrigation pumping system at al-salman district in samawa governorate - Raghad Ali Mejeed; Samah Shyaa Oudah; Rasha Yasen Abed (Institute of Advanced Engineering and Science, 2019)
The seasonal climate changes have direct effects on determination of crop water requirement, irrigation scheduling and the potential of solar energy generation to operate the pumping system for watering crops. This research paper studied the technical evaluation of solar pumping and pressurized drip irrigation systems to investigate the recommended water required for suggested tomatoes crop in area of (one hectare) at AL-Salman district using measured climatic data from AL-Salman Agro-meteorological weather station for a period (2013-2017). The maximum average monthly of solar radiation was 7.6 kWh/m2 at June in all the years of recording data, while the minimum average monthly value was 3.37kWh/m2 at December where the sun at lowest point across the sky. The annual average hours of peak sun that corresponds to the operation time of the pumping system at maximum water consumption was calculated at eight months from March to October with a value of 7.2 hours/day, while it was 5.2 hours/day during the other four months (January, February, November and December). The Solar pumping sizing based on H-Q performance curve of a maximum flow rate of 64.45 m3/h and pump capacity of 16.79 kW with compounds motor pump efficiency of 61.2%. The total water production was 230000 m³/per year which indicates compatible overall system design and adequate to irrigate more planting land with same or other crop types.